O blog como recurso pedagógico para o ensino da Língua Espanhola - Mesquita, Silvana Suelen Mendonça (Instituto Federal do Amazonas, 2018)
This research aimed to verify the blog as an educational resource and its effectiveness in teaching and learning process of Spanish language. With the advent of technologies in the 80s, the society faced challenges in appropriating these TIC among them the Internet and its tools in different contexts today become essential to people's daily lives, including in schools. In this context, the computer and the Internet when used in the classroom are a resource that facilitates the process of teaching and learning, the interaction of the subjects participating and the understanding of the contents taught. Therefore, this research is guided by authors that dialogue on TIC in education and the teaching-learning process of foreign languages, presenting a study focusing on the blog and the teaching of Spanish. For this, we made a bibliographical survey of the route of the TIC in particular the internet with emphasis on the media environment of the blog, its educational use and potential in the teaching-learning of the Spanish Language. Follow the guided sociointeracionismo methodology of Vygotsky a qualitative approach and descriptive character and action research. The results showed the use of the blog as an effective teaching tool, indicating paths and possibilities for teachers to have been a feature that facilitated the learning of reading and writing Spanish Language, thus contributing to education, in interaction environment and writing collaborative with their students, as well as the inclusion of TIC in the classroom, have had a significant importance in their practices, giving new meaning to their planning. Thus, a blog as a pedagogical tool and product of this research was created; allowing the teaching-learning process of the Spanish language becomes more attractive.